Fascism, Catholicism, and Corporatism: the connections between Integralism and Patriotism - Santi Pacheco, Gabriela (2022)
In Brazil, the 1930s were characterized by political transformations that became landmarks in Brazilian politics. The factors that led to this started in the previous decade, amidst changes that were bubbling up during the post-war period and would later alter the national political scenario and the foundations of the First Republic at a structural and ideological level. These changes would leave space for new and diverse political movements to emerge. Some of these movements were directly influenced by the new European authoritarian and corporatist organizations, such as the Action Française and Lusitanian Integralism. This is the case of the neo-monarchical organization, the Brazilian Patrianovist Imperial Action (Ação Imperial Patrianovista Brasileira, AIPB), and the greatest extra-European fascist expression, the Brazilian Integralist Action (Ação Integralista Brasileira, AIB). Based on the understanding that the two movements established connections during this period primarily due to their converging view on the authoritarian, nationalist, and corporatist aspects of their State proposals, the objective of this article is to analyze their contacts and examine the theoretical outlines that served as the foundation of the corporatist proposals of Integralism and Patrianovism, in order to understand their agreements and disagreements.